Security model for microsoft based mobile sales management application in private cloud computing - Kuan, Chee Houng (2013)
The Microsoft-based mobile sales management application is a sales force management application that currently running on Windows Mobile 6.5. It handles sales-related activity and cuts down the administrative task of sales representative. Then, Windows launch a new mobile operating system, Windows Phone and stop providing support to Windows Mobile. This has become an obstacle for Windows Mobile development. From time to time, Windows Mobile will be eliminated from the market due to no support provided by Microsoft. Besides that, Windows Mobile application cannot run on Windows Phone mobile operating system due to lack of compatibility. Therefore, applications those run on Windows Mobile need to find a solution addressing this problem. The rise of cloud computing technology in delivering software as a service becomes a solution. The Microsoft-based mobile sales management application delivers a service to run in a web browser, rather than limited by certain type of mobile that run the Windows Mobile operating system. However, there are some security issues need to concern in order to deliver the Microsoft-based mobile application as a service in private cloud computing. Therefore, security model is needed to answer the security issues in private cloud computing. This research is to propose a security model for the Microsoft-based mobile sales management application in private cloud computing. Lastly, a User Acceptance Test (UAT) is carried out to test the compatibility between proposed security model of Microsoft-based mobile sales management application in a private cloud and tablet computers.